Water-based inorganic energy storage luminous tunnel paint and preparation method thereof

Through material modification and process improvement of the water-based inorganic energy-storage luminous tunnel paint, the problem of reduced performance of the existing luminous tunnel paint in the tunnel environment has been solved, and higher bonding strength, lower afterglow brightness attenuation speed and Longer service life.

CN118994951BActive Publication Date: 2025-01-21JILIN JIANZHU UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411318680.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-21
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

In tunnel environments, the afterglow brightness of existing luminescent tunnel paint has a fast attenuation speed and low combined intensity, resulting in a short service life and is unable to effectively respond to emergency lighting and long-term lighting needs in the tunnel.

Method used

Water-based inorganic energy-storage luminescent tunnel paint is used. The energy-storage luminescent material is treated with weak acid and coated with titanium dioxide to improve the particle surface roughness and bonding strength of the material. In the design of the inner and outer paint, the uniform mixing of raw materials is ensured to avoid agglomeration. phenomenon, enhancing the strength and sound-absorbing effect of the paint film.

Benefits of technology

It significantly reduces the attenuation speed of the afterglow brightness of the inorganic energy-storage luminous tunnel paint, improves the bonding strength and sound-absorbing effect of the material, and extends the service life, making it suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of energy storage luminous road paint, and specifically to water-based inorganic energy storage luminous tunnel paint and a preparation method thereof. The inorganic energy storage luminous tunnel paint is composed of two materials, a surface layer and an inner layer, wherein the surface layer raw materials include alkaline silica sol, silicate solution, silica sand powder, energy storage luminous material, modifier, flame retardant, porous sound-absorbing particles, alumina fiber, dispersant, leveling agent, curing agent, and water. The double-layer inorganic energy storage luminous tunnel paint of the present invention improves the bonding strength between the inorganic energy storage luminous tunnel paint and the wall or base surface, while reducing the attenuation rate of the afterglow brightness of the material. In addition, under the interaction of different materials, the strength of the material and the sound absorption and flame retardant effects are also improved, which is suitable for industrial promotion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy storage luminous tunnel paint, in particular to water-based inorganic energy storage luminous tunnel paint and a preparation method thereof. Background Art

[0002] With the acceleration of highway construction, the proportion of extra-large bridges and extra-long tunnels in the entire project is increasing, which leads to two problems: the longer the tunnel, the more difficult it is to rescue and escape in the event of a traffic accident, especially in the event of a fire, which often causes a power outage in the tunnel lighting circuit, making escape a major difficulty; the longer the tunnel, the more corresponding lighting facilities are equipped, which increases energy consumption. Energy storage luminous road paint can absorb visible light, and then excite it to convert it into visible light emission, playing the role of emergency display; at the same time, it can be used alternately with the lighting facilities in the tunnel to reduce energy consumption. Based on the above characteristics, the use of energy storage luminous road paint in tunnels can improve driving safety and save energy.

[0003] The luminescent materials used in energy storage luminous road paint are currently mainly rare earth activated strontium aluminate series luminescent materials. Compared with traditional zinc sulfide luminescent powder, it has the advantages of non-toxicity, non-radioactivity, high brightness, long afterglow time, long life, stable physical and chemical properties, etc., and can be widely used in many industries. Chinese patent (CN200510085502) discloses a method for preparing rare earth activated strontium aluminate long afterglow phosphor, comprising the following steps: 1) preparing a mixed solution with the following molar fraction ratio: strontium nitrate 29.6-39.5:1, stirring at 120°C for 1-24 hours to form a gel; 2) heating the gel at 300-900°C for 1.5-30 hours to obtain a solid phase pre-calcined product; 3) grinding the solid phase pre-calcined product, adding inorganic salt, and then burning at 800-1400°C in a reducing atmosphere, and washing to obtain the rare earth activated strontium aluminate long afterglow phosphor.

[0004] However, in actual applications, due to the special environment of the tunnel: semi-enclosed and humid, the tunnel paint is greatly affected by the environment, which leads to a decline in the performance of the tunnel paint, the marking lines and marking patterns coated with luminous tunnel paint have a fast attenuation of afterglow brightness, and a short service life.

[0005] Therefore, based on material modification and preparation process improvement technology, this method proposes a water-based inorganic energy storage luminous tunnel paint and a preparation method thereof. The design of the inner and outer layers improves the bonding strength between the inorganic energy storage luminous tunnel paint and the wall or base surface, while reducing the attenuation rate of the afterglow brightness of the material. In addition, the interaction of different materials also improves the strength of the material and the sound absorption and flame retardant effects, making it suitable for industrial promotion. Summary of the invention

[0006] The present invention aims to provide a water-based inorganic energy storage luminous tunnel paint and a preparation method thereof. By improving relevant processes and raw materials, the inorganic energy storage luminous tunnel paint has good gain effects on reducing the attenuation rate of afterglow brightness, material strength, material sound absorption effect and other properties.

[0007] The key points of this method are: 1. In the modification operation of energy storage luminescent materials with titanium dioxide, the energy storage luminescent materials need to be treated with weak acid first to increase the roughness of the surface of the material particles and form pits of different sizes on the surface of the particles. In the subsequent ball milling process, it is beneficial for nano-scale titanium dioxide to be coated on the surface of the energy storage luminescent material. However, the acid treatment time should not be too long to avoid a large amount of dissolution of the energy storage luminescent material; 2. In the preparation of the inner and outer layers of paint, it is necessary to ensure that the various raw materials are mixed evenly to avoid the occurrence of agglomeration. Especially in the preparation of the outer layer of paint, stirring is required in two steps to avoid agglomeration of the raw materials caused by one treatment.

[0008] The specific implementation scheme of the preparation method of the water-based inorganic energy storage luminous tunnel paint according to the present invention is as follows:

[0009] S1. Prepare the surface raw materials according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, flame retardant, porous sound-absorbing particles, alumina fiber, dispersant, leveling agent, curing agent and water;

[0010] Among them, alkaline silica sol 40-60 parts, silicate solution 15-25 parts, silica sand powder 2-4 parts, flame retardant 3-10 parts, porous sound-absorbing particles 5-15 parts, alumina fiber 1-3 parts, dispersant 2-6 parts, leveling agent 2-4 parts, curing agent 4-8 parts, deionized water 40-60 parts;

[0011] The silicate solution is selected from any one of a sodium silicate aqueous solution, a potassium silicate aqueous solution, and a lithium silicate aqueous solution, and the concentration of the silicate solution is 40-50%;

[0012] The flame retardant is a polyphosphate flame retardant;

[0013] The porous sound-absorbing particles are aluminum oxide particles with a particle size of 0.08-0.2 mm and a pore size of 50-100 μm;

[0014] The alumina fiber has a diameter of 6-12 μm and a length of 100-140 μm;

[0015] The dispersant is a fluorocarbon surfactant;

[0016] The leveling agent is polysiloxane;

[0017] The curing agent is polyamide;

[0018] S2. The inner layer raw materials are configured according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent, and water;

[0019] Wherein: 40-60 parts of alkaline silica sol, 15-25 parts of silicate solution, 2-4 parts of silica sand powder, 2-4 parts of alumina fiber, 4-8 parts of dispersant, 4-10 parts of leveling agent, 4-8 parts of curing agent, and 60-100 parts of deionized water;

[0020] The alumina fiber has a diameter of 6-12 μm and a length of 100-140 μm;

[0021] The dispersant is a fluorocarbon surfactant;

[0022] The leveling agent is polysiloxane;

[0023] The curing agent is polyamide;

[0024] S3. The energy storage luminescent material is surface treated with a hydrofluoric acid aqueous solution and then surface modified with a modifier to obtain a modified energy storage luminescent material, which is specifically prepared by the following steps:

[0025] Step 1: Prepare a 0.05-0.1 mol / L hydrofluoric acid aqueous solution, place the energy storage luminescent material in the above-prepared hydrofluoric acid aqueous solution, stir for 30-60 seconds, filter, wash and dry to obtain material a;

[0026] Step 2: Mix the modifier and material a and ball-mill to obtain a modified energy storage luminescent material, with a ball-milling speed of 200-300 rpm;

[0027] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, particle size 30-60μm;

[0028] The modifier is titanium dioxide, with a particle size of 3-10 nm and rutile type;

[0029] The mass ratio of the modifier to material a is (2-3):(20-30);

[0030] The usage ratio of the energy storage luminescent material to the hydrofluoric acid aqueous solution is (1.5-2.5) g: (45-55) mL.

[0031] S4. The surface raw material and the modified energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint;

[0032] Step 1: add alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 200-300rpm and the processing time is 2-4h;

[0033] Step 2: Add modified energy storage luminescent material, flame retardant and porous sound absorbing particles to the mixed solution of the first step and continue planetary ball milling for 1-2 hours to obtain the outer layer paint of inorganic energy storage luminescent tunnel;

[0034] The usage ratio of the surface raw material to the modified energy storage luminescent material is 6-7:0.8-1.

[0035] S5. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint;

[0036] Alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water are added together and mixed by planetary ball mill to obtain inorganic energy storage luminous tunnel inner layer paint. The ball mill speed is 200-300rpm and the processing time is 2-4h.

[0037] S6. The inorganic energy storage luminous tunnel outer layer paint and the inorganic energy storage luminous tunnel inner layer paint are respectively put into cans to obtain water-based inorganic energy storage luminous tunnel paint.

[0038] Beneficial effects:

[0039] (1) The method of the present invention adopts a double-layer structural design, wherein the inner layer of paint has a low viscosity and a good wetting effect, which can effectively improve the bonding strength between the paint and the wall;

[0040] (2) In the method of the present invention, the surface modification of the energy storage luminescent material can reduce the decay rate of the afterglow brightness of the final paint. In addition, the alumina fiber added to the paint also has an effect of improving the strength of the paint.

[0041] (3) In the method of the present invention, porous sound-absorbing particles are added to the surface paint. Since the surface slurry has a high viscosity and cannot penetrate into the porous sound-absorbing particles, a relatively closed structure is formed inside the sound-absorbing particles after curing, which can achieve a good sound-absorbing effect. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] The raw materials used in the embodiments of the present invention are as follows:

[0044] Silica sand powder (Hebei Zongrun Mineral Products Co., Ltd., diameter 50-70mm, specific surface area 400-450m 2 / kg);

[0045] Polyphosphate flame retardant (valid from Hubei Langbowan Biopharmaceutical Co., Ltd., model number 115-86-6);

[0046] Fluorocarbon surfactant (Jinan Guochen Taifu Chemical Co., Ltd., model TT-310);

[0047] Polysiloxane (Dongguan Suguang Plastic Raw Materials Co., Ltd., model ARCS-60D);

[0048] Polyamide (Shanghai Xuanya Biotechnology Co., Ltd., model number is xY14142);

[0049] Alkaline silica sol: purchased from Qinghe Chaotai Metal Materials Co., Ltd., model number is VK-S01A.

[0050] The silicate solution is a sodium silicate aqueous solution, and the mass concentration of the sodium silicate aqueous solution is 45%.

[0051] As an embodiment, the following content of the embodiments of the present invention gives several specific examples of the preparation method of the aforementioned water-based inorganic energy storage luminous tunnel paint for comparison and explanation.

[0052] Embodiment 1:

[0053] S1. Configure the surface materials by mass: 40 parts of alkaline silica sol, 15 parts of silicate solution, 2 parts of silica sand powder, 3 parts of flame retardant, 5 parts of porous sound-absorbing particles, 1 part of alumina fiber, 2 parts of dispersant, 2 parts of leveling agent, 4 parts of curing agent, and 40 parts of deionized water;

[0054] The flame retardant is a polyphosphate flame retardant;

[0055] The porous sound-absorbing particles are aluminum oxide particles with an average particle size of 0.08 mm and an average pore size of 50 μm, produced by Ningbo Beijiaer New Materials Co., Ltd., model 1344-28-1;

[0056] The alumina fibers have an average diameter of 6 μm and an average length of 100 μm;

[0057] The dispersant is a fluorocarbon surfactant;

[0058] The leveling agent is polysiloxane;

[0059] The curing agent is polyamide;

[0060] S2. The inner layer raw materials are configured by mass: 40 parts of alkaline silica sol, 15 parts of silicate solution, 2 parts of silica sand powder, 2 parts of alumina fiber, 4 parts of dispersant, 4 parts of leveling agent, 4 parts of curing agent, and 60 parts of deionized water;

[0061] The alumina fibers have an average diameter of 6 μm and an average length of 100 μm;

[0062] The dispersant is a fluorocarbon surfactant;

[0063] The leveling agent is polysiloxane;

[0064] The curing agent is polyamide;

[0065] S3. The energy storage luminescent material is surface treated with a hydrofluoric acid aqueous solution and then surface modified with a modifier to obtain a modified energy storage luminescent material, which is specifically prepared by the following steps:

[0066] Step 1: Prepare 0.05 mol / L hydrofluoric acid aqueous solution, place 1.5 g of energy storage luminescent material in 45 mL of the above-prepared hydrofluoric acid aqueous solution, stir for 40 seconds, filter, wash and dry to obtain material a;

[0067] Step 2: 2g of the modifier and 20g of material a are mixed and ball-milled to obtain a modified energy storage luminescent material, and the ball-milling speed is 200rpm;

[0068] The ratio of the energy storage luminescent material to the hydrofluoric acid aqueous solution is 1.5 g:45 mL;

[0069] The mass ratio of the modifier to material a is 2:20;

[0070] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, average particle size 30 μm, Guangzhou Nonferrous Metals Research Institute;

[0071] The modifier is titanium dioxide, with an average particle size of 3nm and rutile type;

[0072] S4. The surface raw material and the modified energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint; the specific preparation method is:

[0073] Step 1: add alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 200 rpm and the processing time is 2 hours.

[0074] Step 2: adding modified energy storage luminescent material, flame retardant and porous sound absorbing particles to the mixed solution of the first step and continuing planetary ball milling for 1 hour to obtain the outer layer paint of inorganic energy storage luminescent tunnel;

[0075] The ratio of the surface raw material to the modified energy storage luminescent material is 6:0.8;

[0076] S5. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint; the specific preparation method is:

[0077] Alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water are added together and mixed by planetary ball mill to obtain inorganic energy storage luminous tunnel inner layer paint. The ball milling speed is 200 rpm and the processing time is 2 hours.

[0078] S6. The inorganic energy storage luminous tunnel outer layer paint and the inorganic energy storage luminous tunnel inner layer paint are respectively put into cans to obtain water-based inorganic energy storage luminous tunnel paint.

[0079] Embodiment 2:

[0080] S1. Prepare the surface raw materials according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, flame retardant, porous sound-absorbing particles, alumina fiber, dispersant, leveling agent, curing agent and water;

[0081] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 7 parts of flame retardant, 10 parts of porous sound-absorbing particles, 2 parts of alumina fiber, 4 parts of dispersant, 3 parts of leveling agent, 6 parts of curing agent, and 50 parts of deionized water;

[0082] The flame retardant is a polyphosphate flame retardant;

[0083] The porous sound-absorbing particles are aluminum oxide particles with an average particle size of 0.1 mm and an average pore size of 80 μm, produced by Ningbo Beijiaer New Materials Co., Ltd., model 1344-28-1;

[0084] The alumina fibers have an average diameter of 10 μm and an average length of 120 μm;

[0085] The dispersant is a fluorocarbon surfactant;

[0086] The leveling agent is polysiloxane;

[0087] The curing agent is polyamide;

[0088] S2. The inner layer raw materials are configured according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent, and water;

[0089] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 3 parts of alumina fiber, 6 parts of dispersant, 8 parts of leveling agent, 6 parts of curing agent, and 80 parts of deionized water;

[0090] The alumina fiber has a diameter of 10 μm and a length of 120 μm;

[0091] The dispersant is a fluorocarbon surfactant;

[0092] The leveling agent is polysiloxane;

[0093] The curing agent is polyamide;

[0094] S3. The energy storage luminescent material is surface treated with a hydrofluoric acid aqueous solution and then surface modified with a modifier to obtain a modified energy storage luminescent material, which is specifically prepared by the following steps:

[0095] Step 1: Prepare 0.08 mol / L hydrofluoric acid aqueous solution, place 2 g of energy storage luminescent material in 50 mL of the above-prepared hydrofluoric acid aqueous solution, stir for 40 seconds, filter, wash and dry to obtain material a;

[0096] Step 2: 2.5 g of the modifier and 25 g of material a were mixed and ball-milled to obtain a modified energy storage luminescent material, and the ball-milling speed was 250 rpm;

[0097] The ratio of the energy storage luminescent material to the hydrofluoric acid aqueous solution is 2g:50mL;

[0098] The mass ratio of the modifier to material a is 2.5:25;

[0099] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, average particle size 40 μm, Guangzhou Nonferrous Metals Research Institute;

[0100] The modifier is titanium dioxide, with an average particle size of 8nm and rutile type;

[0101] S4. The surface raw material and the modified energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint; the specific preparation method is:

[0102] Step 1: add alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0103] Step 2: adding modified energy storage luminescent material, flame retardant and porous sound absorbing particles to the mixed solution of the first step and continuing planetary ball milling for 1.5 hours to obtain the outer layer paint of inorganic energy storage luminescent tunnel;

[0104] The ratio of the surface raw material to the modified energy storage luminescent material is 6.5:0.9;

[0105] S5. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint; the specific preparation method is:

[0106] Alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water are added together and mixed by planetary ball mill to obtain inorganic energy storage luminous tunnel inner layer paint. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0107] S6. The inorganic energy storage luminous tunnel outer layer paint and the inorganic energy storage luminous tunnel inner layer paint are respectively put into cans to obtain water-based inorganic energy storage luminous tunnel paint.

[0108] Embodiment 3:

[0109] S1. Prepare the surface raw materials according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, energy storage luminescent material, modifier, flame retardant, porous sound absorbing particles, alumina fiber, dispersant, leveling agent, curing agent and water;

[0110] Among them, 60 parts of alkaline silica sol, 25 parts of silicate solution, 4 parts of silica sand powder, 10 parts of flame retardant, 15 parts of porous sound-absorbing particles, 3 parts of alumina fiber, 6 parts of dispersant, 4 parts of leveling agent, 8 parts of curing agent, and 60 parts of deionized water;

[0111] The flame retardant is a polyphosphate flame retardant;

[0112] The porous sound-absorbing particles are aluminum oxide particles with an average particle size of 0.2 mm and an average pore size of 100 μm, from Ningbo Beijiaer New Materials Co., Ltd., model 1344-28-1;

[0113] The alumina fibers have an average diameter of 12 μm and an average length of 140 μm;

[0114] The dispersant is a fluorocarbon surfactant;

[0115] The leveling agent is polysiloxane;

[0116] The curing agent is polyamide;

[0117] S2. The inner layer raw materials are configured according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent, and water;

[0118] Among them, 60 parts of alkaline silica sol, 25 parts of silicate solution, 4 parts of silica sand powder, 4 parts of alumina fiber, 8 parts of dispersant, 10 parts of leveling agent, 8 parts of curing agent, and 100 parts of deionized water;

[0119] The alumina fiber has a diameter of 12 μm and a length of 140 μm;

[0120] The dispersant is a fluorocarbon surfactant;

[0121] The leveling agent is polysiloxane;

[0122] The curing agent is polyamide;

[0123] S3. The energy storage luminescent material is surface treated with a hydrofluoric acid aqueous solution and then surface modified with a modifier to obtain a modified energy storage luminescent material, which is specifically prepared by the following steps:

[0124] Step 1: Prepare 0.1 mol / L hydrofluoric acid aqueous solution, place 2.5 g of energy storage luminescent material in 55 mL of the above-prepared hydrofluoric acid aqueous solution, stir for 40 seconds, filter, wash and dry to obtain material a;

[0125] Step 2: 3 g of the modifier and 30 g of material a were mixed and ball-milled to obtain a modified energy storage luminescent material, and the ball-milling speed was 300 rpm;

[0126] The ratio of the energy storage luminescent material to the hydrofluoric acid aqueous solution is 2.5 g:55 mL;

[0127] The ratio of the energy storage luminescent material to the hydrofluoric acid aqueous solution is 2.5 g:55 mL;

[0128] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, average particle size 60 μm, Guangzhou Nonferrous Metals Research Institute;

[0129] The modifier is titanium dioxide, with an average particle size of 10 nm and a rutile type.

[0130] S4. The surface raw material and the modified energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint; the specific preparation method is:

[0131] Step 1: add alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 300 rpm and the processing time is 4 hours.

[0132] Step 2: adding modified energy storage luminescent material, flame retardant and porous sound absorbing particles to the mixed solution of the first step and continuing planetary ball milling for 2 hours to obtain the outer layer paint of inorganic energy storage luminescent tunnel;

[0133] The ratio of the surface raw material to the modified energy storage luminescent material is 7:1;

[0134] S5. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint; the specific preparation method is:

[0135] Alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water are added together and mixed by planetary ball mill to obtain inorganic energy storage luminous tunnel inner layer paint. The ball milling speed is 300 rpm and the processing time is 4 hours.

[0136] S6. The inorganic energy storage luminous tunnel outer layer paint and the inorganic energy storage luminous tunnel inner layer paint are respectively put into cans to obtain water-based inorganic energy storage luminous tunnel paint.

[0137] Comparative Example 1:

[0138] S1. Prepare the surface raw materials according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, energy storage luminescent material, flame retardant, porous sound absorbing particles, alumina fiber, dispersant, leveling agent, curing agent and water;

[0139] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 25 parts of energy storage luminescent material, 7 parts of flame retardant, 10 parts of porous sound-absorbing particles, 2 parts of alumina fiber, 4 parts of dispersant, 3 parts of leveling agent, 6 parts of curing agent, and 50 parts of deionized water;

[0140] The flame retardant is a polyphosphate flame retardant;

[0141] The porous sound-absorbing particles are aluminum oxide particles with an average particle size of 0.1 mm and an average pore size of 80 μm, produced by Ningbo Beijiaer New Materials Co., Ltd., model 1344-28-1;

[0142] The alumina fibers have an average diameter of 10 μm and an average length of 120 μm;

[0143] The dispersant is a fluorocarbon surfactant;

[0144] The leveling agent is polysiloxane;

[0145] The curing agent is polyamide;

[0146] S2. The inner layer raw materials are configured according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent, and water;

[0147] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 3 parts of alumina fiber, 6 parts of dispersant, 8 parts of leveling agent, 6 parts of curing agent, and 80 parts of deionized water;

[0148] The alumina fiber has a diameter of 8 μm and a length of 120 μm;

[0149] The dispersant is a fluorocarbon surfactant;

[0150] The leveling agent is polysiloxane;

[0151] The curing agent is polyamide;

[0152] S3. The surface raw material and the energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint; the specific preparation method is:

[0153] Step 1: add alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0154] Step 2: adding energy storage luminescent material, flame retardant and porous sound absorbing particles to the mixed solution of the first step and continuing planetary ball milling for 1.5 hours to obtain the inorganic energy storage luminescent tunnel outer layer paint;

[0155] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, average particle size 40 μm, Guangzhou Nonferrous Metals Research Institute;

[0156] The ratio of the surface raw material to the modified energy storage luminescent material is 6.5:0.9;

[0157] S4. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint; the specific preparation method is:

[0158] Alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water are added together and mixed by planetary ball mill to obtain inorganic energy storage luminous tunnel inner layer paint. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0159] Comparative Example 2:

[0160] S1. Prepare the surface raw materials according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, flame retardant, alumina fiber, dispersant, leveling agent, curing agent and water;

[0161] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 7 parts of flame retardant, 2 parts of alumina fiber, 4 parts of dispersant, 3 parts of leveling agent, 6 parts of curing agent, and 50 parts of deionized water;

[0162] The flame retardant is a polyphosphate flame retardant;

[0163] The alumina fibers have an average diameter of 10 μm and an average length of 120 μm;

[0164] The dispersant is a fluorocarbon surfactant;

[0165] The leveling agent is polysiloxane;

[0166] The curing agent is polyamide;

[0167] S2. The inner layer raw materials are configured according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent, and water;

[0168] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 3 parts of alumina fiber, 6 parts of dispersant, 8 parts of leveling agent, 6 parts of curing agent, and 80 parts of deionized water;

[0169] The alumina fiber has a diameter of 10 μm and a length of 120 μm;

[0170] The dispersant is a fluorocarbon surfactant;

[0171] The leveling agent is polysiloxane;

[0172] The curing agent is polyamide;

[0173] S3. The energy storage luminescent material is surface treated with a hydrofluoric acid aqueous solution and then surface modified with a modifier to obtain a modified energy storage luminescent material, which is specifically prepared by the following steps:

[0174] Step 1: Prepare 0.08 mol / L hydrofluoric acid aqueous solution, place 2 g of energy storage luminescent material in 50 mL of the above-prepared hydrofluoric acid aqueous solution, stir for 40 seconds, filter, wash and dry to obtain material a;

[0175] Step 2: 2g of the modifier and 25g of material a are mixed and ball-milled to obtain a modified energy storage luminescent material, and the ball-milling speed is 250rpm;

[0176] The ratio of the energy storage luminescent material to the hydrofluoric acid aqueous solution is 2g:50mL;

[0177] The mass ratio of the modifier to material a is 2.5:25;

[0178] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, average particle size 40 μm, Guangzhou Nonferrous Metals Research Institute;

[0179] The modifier is titanium dioxide, with an average particle size of 8nm and rutile type;

[0180] S4. The surface raw material and the modified energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint; the specific preparation method is:

[0181] Step 1: add alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0182] Step 2: adding the modified energy storage luminescent material and the flame retardant to the mixed solution of the first step and continuing the planetary ball milling for 1.5 hours to obtain the inorganic energy storage luminescent tunnel outer layer paint;

[0183] The ratio of the surface raw material to the modified energy storage luminescent material is 6.5:0.9;

[0184] S5. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint; the specific preparation method is:

[0185] Alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water are added together and mixed by planetary ball mill to obtain inorganic energy storage luminous tunnel inner layer paint. The ball milling speed is 250 rpm and the processing time is 3 hours.

[0186] S6. The inorganic energy storage luminous tunnel outer layer paint and the inorganic energy storage luminous tunnel inner layer paint are respectively put into cans to obtain water-based inorganic energy storage luminous tunnel paint.

[0187] Comparative Example 3:

[0188] S1. Prepare the surface raw materials according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, flame retardant, porous sound-absorbing particles, dispersant, leveling agent, curing agent and water;

[0189] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 7 parts of flame retardant, 10 parts of porous sound-absorbing particles, 2 parts of alumina fiber, 4 parts of dispersant, 3 parts of leveling agent, 6 parts of curing agent, and 50 parts of deionized water;

[0190] The flame retardant is a polyphosphate flame retardant;

[0191] The porous sound-absorbing particles are aluminum oxide particles with an average particle size of 0.1 mm and an average pore size of 80 μm, produced by Ningbo Beijiaer New Materials Co., Ltd., model 1344-28-1;

[0192] The alumina fibers have an average diameter of 10 μm and an average length of 120 μm.

[0193] The dispersant is a fluorocarbon surfactant;

[0194] The leveling agent is polysiloxane;

[0195] The curing agent is polyamide;

[0196] S2. The inner layer raw materials are configured according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent, and water;

[0197] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 6 parts of dispersant, 8 parts of leveling agent, 6 parts of curing agent, and 80 parts of deionized water;

[0198] The dispersant is a fluorocarbon surfactant;

[0199] The leveling agent is polysiloxane;

[0200] The curing agent is polyamide;

[0201] S3. After the energy storage luminescent material is surface treated with an aqueous hydrofluoric acid solution, the surface is modified by a modifier to obtain a modified energy storage luminescent material;

[0202] Step 1: Prepare 0.08 mol / L weak hydrofluoric acid aqueous solution, place 2 g of energy storage luminescent material in 50 mL of the above-prepared hydrofluoric acid aqueous solution, stir for 40 seconds, filter, wash and dry to obtain material a;

[0203] Step 2: 2g of the modifier and 25g of material a are mixed and planetarily ball-milled to obtain a modified energy storage luminescent material, and the ball milling speed is 250rpm;

[0204] The ratio of the energy storage luminescent material to the hydrofluoric acid aqueous solution is 2g:50mL;

[0205] The mass ratio of the modifier to material a is 2.5:25;

[0206] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, particle size 40μm;

[0207] The modifier is titanium dioxide, with a particle size of 8nm and rutile type;

[0208] S4. The surface raw material and the modified energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint; the specific preparation method is:

[0209] Step 1: add alkaline silica sol, silicate solution, silica sand powder, dispersant, leveling agent, curing agent and water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0210] Step 2: adding modified energy storage luminescent material, flame retardant and porous sound absorbing particles to the mixed solution of the first step and continuing planetary ball milling for 1.5 hours to obtain the outer layer paint of inorganic energy storage luminescent tunnel;

[0211] The ratio of the surface raw material to the modified energy storage luminescent material is 6.5:0.9;

[0212] S5. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint; the specific preparation method is:

[0213] Alkaline silica sol, silicate solution, silica sand powder, dispersant, leveling agent, curing agent and water are added together and mixed by planetary ball mill to obtain inorganic energy storage luminous tunnel inner layer paint. The ball milling speed is 250 rpm and the processing time is 3 hours.

[0214] S6. The inorganic energy storage luminous tunnel outer layer paint and the inorganic energy storage luminous tunnel inner layer paint are respectively put into cans to obtain water-based inorganic energy storage luminous tunnel paint.

[0215] Comparative Example 4:

[0216] S1. Prepare the raw materials in proportion by mass, including alkaline silica sol, silicate solution, silica sand powder, flame retardant, porous sound-absorbing particles, alumina fiber, dispersant, leveling agent, curing agent and water;

[0217] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 7 parts of flame retardant, 10 parts of porous sound-absorbing particles, 2 parts of alumina fiber, 4 parts of dispersant, 3 parts of leveling agent, 6 parts of curing agent, and 50 parts of deionized water;

[0218] The flame retardant is a polyphosphate flame retardant;

[0219] The porous sound-absorbing particles are aluminum oxide particles with an average particle size of 0.1 mm and an average pore size of 80 μm, produced by Ningbo Beijiaer New Materials Co., Ltd., model 1344-28-1;

[0220] The alumina fibers have an average diameter of 10 μm and an average length of 120 μm;

[0221] The dispersant is a fluorocarbon surfactant;

[0222] The leveling agent is polysiloxane;

[0223] The curing agent is polyamide;

[0224] S2. The energy storage luminescent material is surface treated with a hydrofluoric acid aqueous solution and then surface modified with a modifier to obtain a modified energy storage luminescent material, which is specifically prepared by the following steps:

[0225] Step 1: Prepare 0.08 mol / L hydrofluoric acid aqueous solution, place 2 g of energy storage luminescent material in 50 mL of the above-prepared hydrofluoric acid aqueous solution, stir for 40 seconds, filter, wash and dry to obtain material a;

[0226] Step 2: 2g of the modifier and 25g of material a are mixed and ball-milled to obtain a modified energy storage luminescent material, and the ball-milling speed is 250rpm;

[0227] The ratio of the energy storage luminescent material to the hydrofluoric acid aqueous solution is 2g:50mL;

[0228] The mass ratio of the modifier to material a is 2.5:25;

[0229] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, average particle size 40 μm, Guangzhou Nonferrous Metals Research Institute;

[0230] The modifier is titanium dioxide, with an average particle size of 8nm and rutile type;

[0231] S3. The raw materials configured in step S1 are stirred and mixed with the modified energy storage luminescent material to prepare an inorganic energy storage luminescent tunnel paint; the specific preparation method is:

[0232] Step 1: add alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0233] Step 2: Add modified energy storage luminescent material, flame retardant and porous sound absorbing particles to the mixed solution of the first step and continue planetary ball milling for 1.5 hours to obtain inorganic energy storage luminescent tunnel paint;

[0234] The ratio of the raw material to the modified energy storage luminescent material prepared in step S1 is 6.5:0.9.

[0235] Comparative Example 5:

[0236] S1. Prepare the surface raw materials according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, flame retardant, porous sound-absorbing particles, alumina fiber, dispersant, leveling agent, curing agent and water;

[0237] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 7 parts of flame retardant, 10 parts of porous sound-absorbing particles, 2 parts of alumina fiber, 4 parts of dispersant, 3 parts of leveling agent, 6 parts of curing agent, and 50 parts of deionized water;

[0238] The flame retardant is a polyphosphate flame retardant;

[0239] The porous sound-absorbing particles are aluminum oxide particles with an average particle size of 0.1 mm and an average pore size of 80 μm, produced by Ningbo Beijiaer New Materials Co., Ltd., model 1344-28-1;

[0240] The alumina fibers have an average diameter of 10 μm and an average length of 120 μm;

[0241] The dispersant is a fluorocarbon surfactant;

[0242] The leveling agent is polysiloxane;

[0243] The curing agent is polyamide;

[0244] S2. The inner layer raw materials are configured according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent, and water;

[0245] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 3 parts of alumina fiber, 6 parts of dispersant, 8 parts of leveling agent, 6 parts of curing agent, and 80 parts of deionized water;

[0246] The alumina fibers have an average diameter of 10 μm and an average length of 120 μm;

[0247] The dispersant is a fluorocarbon surfactant;

[0248] The leveling agent is polysiloxane;

[0249] The curing agent is polyamide;

[0250] S3. The energy storage luminescent material is surface-modified by a modifier to obtain a modified energy storage luminescent material, which is specifically prepared by the following steps:

[0251] 2 g of the modifier and 25 g of the energy storage luminescent material were mixed and planetary ball milled to obtain the modified energy storage luminescent material, and the ball milling speed was 250 rpm;

[0252] The modifier is titanium dioxide, with an average particle size of 8nm and rutile type;

[0253] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, average particle size 40 μm, Guangzhou Nonferrous Metals Research Institute;

[0254] S4. The surface raw material and the modified energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint; the specific preparation method is:

[0255] Step 1: add alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0256] Step 2: adding modified energy storage luminescent material, flame retardant and porous sound absorbing particles to the mixed solution of the first step and continuing planetary ball milling for 1.5 hours to obtain the outer layer paint of inorganic energy storage luminescent tunnel;

[0257] The ratio of the surface raw material to the modified energy storage luminescent material is 6.5:0.9;

[0258] S5. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint; the specific preparation method is:

[0259] Alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water are added together and mixed by planetary ball mill to obtain inorganic energy storage luminous tunnel inner layer paint. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0260] S6. The inorganic energy storage luminous tunnel outer layer paint and the inorganic energy storage luminous tunnel inner layer paint are respectively put into cans to obtain water-based inorganic energy storage luminous tunnel paint.

[0261] Comparative Example 6:

[0262] S1. Prepare the surface raw materials according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, flame retardant, porous sound-absorbing particles, alumina fiber, dispersant, leveling agent, curing agent and water;

[0263] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 7 parts of flame retardant, 10 parts of porous sound-absorbing particles, 2 parts of alumina fiber, 4 parts of dispersant, 3 parts of leveling agent, 6 parts of curing agent, and 50 parts of deionized water;

[0264] The flame retardant is a polyphosphate flame retardant;

[0265] The porous sound-absorbing particles are aluminum oxide particles with an average particle size of 0.1 mm and an average pore size of 80 μm, produced by Ningbo Beijiaer New Materials Co., Ltd., model 1344-28-1;

[0266] The alumina fibers have an average diameter of 10 μm and an average length of 120 μm;

[0267] The dispersant is a fluorocarbon surfactant;

[0268] The leveling agent is polysiloxane;

[0269] The curing agent is polyamide;

[0270] S2. The inner layer raw materials are configured according to the mass ratio, including alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent, and water;

[0271] Among them, 50 parts of alkaline silica sol, 20 parts of silicate solution, 3 parts of silica sand powder, 3 parts of alumina fiber, 6 parts of dispersant, 8 parts of leveling agent, 6 parts of curing agent, and 80 parts of deionized water;

[0272] The alumina fibers have an average diameter of 10 μm and an average length of 120 μm;

[0273] The dispersant is a fluorocarbon surfactant;

[0274] The leveling agent is polysiloxane;

[0275] The curing agent is polyamide;

[0276] S3. The energy storage luminescent material is surface treated with a hydrofluoric acid aqueous solution and then surface modified with a modifier to obtain a modified energy storage luminescent material, which is specifically prepared by the following steps:

[0277] Step 1: Prepare 0.08 mol / L weak hydrofluoric acid aqueous solution, place 2 g of energy storage luminescent material in 50 mL of the above-prepared hydrofluoric acid aqueous solution, stir for 40 seconds, filter, wash and dry to obtain material a;

[0278] Step 2: 2.5 g of the modifier and 25 g of material a were mixed and planetary ball milled to obtain a modified energy storage luminescent material, and the ball milling speed was 250 rpm;

[0279] The ratio of the energy storage luminescent material to the hydrofluoric acid aqueous solution is 2g:50mL;

[0280] The mass ratio of the modifier to material a is 2.5:25;

[0281] The energy storage luminescent material is SrAl2O4:Eu 2+ ,Dy 3+ Fluorite powder, average particle size 30 μm, Guangzhou Nonferrous Metals Research Institute;

[0282] The modifier is titanium dioxide, with an average particle size of 3nm and rutile type.

[0283] S4. The surface raw material and the modified energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint; the specific preparation method is:

[0284] Alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, modified energy storage luminescent material, flame retardant, porous sound absorbing particles, leveling agent, curing agent and water are added together and mixed by planetary ball milling to obtain inorganic energy storage luminescent tunnel outer layer paint. The ball milling speed is 250 rpm and the processing time is 3 hours.

[0285] The ratio of the surface raw material to the modified energy storage luminescent material is 6.5:0.9;

[0286] S5. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint; the specific preparation method is:

[0287] Alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and water are added together and mixed by planetary ball mill to obtain inorganic energy storage luminous tunnel inner layer paint. The ball mill speed is 250 rpm and the processing time is 3 hours.

[0288] S6. The inorganic energy storage luminous tunnel outer layer paint and the inorganic energy storage luminous tunnel inner layer paint are respectively put into cans to obtain water-based inorganic energy storage luminous tunnel paint.

[0289] The sound absorption level is usually divided into five levels, which are divided according to the sound insulation effect of the sound absorbing material, as follows:

[0290] Level 1: The sound insulation effect is weak, and can only isolate 5 to 10 decibels of noise;

[0291] Level 2: The sound insulation ability is improved and can block 15 to 20 decibels of noise;

[0292] Level 3: The combination of aluminum alloy and insulating glass can effectively isolate 25 to 30 decibels of noise;

[0293] Level 4: Can block 35 to 40 decibels of noise;

[0294] Level 5: The best sound insulation effect, which can block 45 to 50 decibels of noise;

[0295] In the water-based inorganic energy storage luminous tunnel paint prepared above, the inorganic energy storage luminous tunnel inner layer paint is coated on the tunnel surface, and after curing at 60-80° C., the inorganic energy storage luminous tunnel outer layer paint is coated, and cured at 60-80° C. to obtain a coating coated with the water-based inorganic energy storage luminous tunnel paint, and the coating is tested for performance;

[0296] The coating coated with water-based inorganic energy storage luminous tunnel paint is placed in a dark environment, and the glossiness of the water-based inorganic energy storage luminous tunnel paint is measured by a gloss meter. The gloss meter calculates the relative glossiness at 2h, 6h, and 10h by comparing the difference between the reflection angle of the standard light source and the reflection angle of the test sample. The relative glossiness is (%) = test sample reflection angle / standard light source reflection angle;

[0297] The standard for material sound absorption test can refer to GB / T 20247 (Sound absorption performance test of building materials);

[0298] tensile strength:

[0299] Tensile strength is the resistance to the maximum uniform plastic deformation of a material. Before the tensile specimen is subjected to the maximum tensile stress, the deformation is uniform and consistent, but after exceeding the maximum tensile stress, the metal begins to shrink, that is, concentrated deformation occurs. For brittle materials with no (or very small) uniform plastic deformation, it reflects the material's resistance to fracture. The test standard can refer to the national standard GB / T9779-2015 "Test Method for Tensile Properties of Cement Coatings".

[0300] The test results are shown in Table 1.

[0301] Table 1: Test results

[0302]

[0303]

[0304] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a water-based inorganic energy storage luminous tunnel paint, characterized in that: The steps include: S1. Prepare the surface raw materials according to the mass ratio: the composition and mass proportion of the surface raw materials are: 40-60 parts of alkaline silica sol, 15-25 parts of silicate solution, 2-4 parts of silica sand powder, 3-10 parts of flame retardant, 5-15 parts of porous sound-absorbing particles, 1-3 parts of alumina fiber, 2-6 parts of dispersant, 2-4 parts of leveling agent, 4-8 parts of curing agent, 40-60 parts of deionized water; wherein the flame retardant is a polyphosphate flame retardant; the porous sound-absorbing particles are alumina particles with a particle size of 0.08-0.2mm and a pore size of 50-100μm; the curing agent is polyamide; S2. The inner layer raw materials are configured according to the mass ratio: the composition and mass proportion of the inner layer raw materials are: 40-60 parts of alkaline silica sol, 15-25 parts of silicate solution, 2-4 parts of silica sand powder, 2-4 parts of alumina fiber, 4-8 parts of dispersant, 4-10 parts of leveling agent, 4-8 parts of curing agent, and 60-100 parts of deionized water; wherein the curing agent is polyamide; S3. Surface modification of the energy storage luminescent material to obtain a modified energy storage luminescent material, specifically comprising: Step 1: Prepare a 0.05-0.1 mol / L hydrofluoric acid aqueous solution, place the energy storage luminescent material in the above-prepared hydrofluoric acid aqueous solution, stir for 30-60 seconds, filter, wash and dry to obtain material a; Step 2: Mix the modifier and material a and ball-mill to obtain a modified energy storage luminescent material, with a ball-milling speed of 200-300 rpm; Wherein, the energy storage luminescent material is SrAl2O4: Eu 2+ ,Dy 3+ Fluorite powder, particle size 30-60 μm; the modifier is titanium dioxide, particle size 3-10 nm, rutile type; the mass ratio of the modifier to material a is (2-3): (20-30); S4. The surface raw material and the modified energy storage luminescent material are stirred and mixed to prepare an inorganic energy storage luminescent tunnel outer layer paint, specifically comprising: Step 1: add alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent and deionized water together, and mix them by planetary ball mill to obtain a mixed solution. The ball mill speed is 200-300rpm and the processing time is 2-4h; Step 2: Add modified energy storage luminescent material, flame retardant and porous sound absorbing particles to the mixed solution of the first step and continue to ball mill for 1-2 hours to obtain the outer layer paint of inorganic energy storage luminescent tunnel; The ratio of the surface raw material to the modified energy storage luminescent material is 6-7:0.8-1; S5. The inner raw materials are stirred and mixed to obtain an inorganic energy storage luminous tunnel inner layer paint; S6. The inorganic energy storage luminous tunnel outer layer paint and the inorganic energy storage luminous tunnel inner layer paint are respectively put into cans to obtain water-based inorganic energy storage luminous tunnel paint.

2. The preparation method according to claim 1, characterized in that: The silicate solution is selected from any one of a sodium silicate aqueous solution, a potassium silicate aqueous solution, and a lithium silicate aqueous solution, and the concentration of the silicate solution is 40-50%; The alumina fiber has a diameter of 6-12 μm and a length of 100-140 μm; The dispersant is a fluorocarbon surfactant; The leveling agent is polysiloxane.

3. The preparation method according to claim 1, characterized in that: In step S5, a process for preparing an inorganic energy storage luminous tunnel inner layer paint is performed by stirring and mixing, including: adding alkaline silica sol, silicate solution, silica sand powder, alumina fiber, dispersant, leveling agent, curing agent, and deionized water together, and mixing them by ball milling to obtain an inorganic energy storage luminous tunnel inner layer paint, the ball milling speed is 200-300rpm, and the processing time is 2-4h.

4. A water-based inorganic energy storage luminous tunnel paint prepared according to the preparation method according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Process for preparing rare-earth excited strontium aluminate long afterglow fluorescent powder

    CN1900216A

  • Inorganic water-based energy-storage luminescent paint for tunnels and preparation method

    CN108084752A

  • Sound-absorbing and heat-insulating inorganic particle composite board

    CN221417624U